Predição de enchimento de barragem por meio de modelagem hidrológica na bacia hidrológica na bacia hidrográfica do Rio Poxim-Açu-SE - Almeida, Carlos Alberto Prata de (2013)
Nowadays, the hydrologic modeling has become an essential tool for predicting the hydrodynamic behavior in a watershed due to the importance of the detailed estimative of the water balance for environmental management in a sustainable manner. However, the phenomena involved in this cycle have large spatial and temporal variations, which complicates their estimation. In this context, the objectives set for this study is the evaluation of the production of water - river Poxim açu , using the SWAT hydrological model (Soil and Water Assessmente Tool) . The calibration model was manually performed for a period in the year 2012, considering some relevant geological aspects of the basin under study, resulting in a calibration option from related to groundwater flow parameters and obtaining results NSE (0,73), PBIAS (-9,86) and RSR (0.52) . Were performed validation procedures which observed similarities between the results of water production with the results obtained by Silva (2013) for the same watershed in 2011. The model was used for predictive simulation of filling the dam Syndicalist Jaime Umbelino de Souza at river Poxim-açu, besides being subjected to simulations with rainfall data from rainfall stations in the municipalities of Itaporanga D´Ajuda and Aracaju to reviews of water production responses. The result was satisfactory, with fit temporal very good between recorded predictive filling and filling. The study concludes that the SWAT model applies satisfactorily in performing predictive simulations of water production in the basin of Poxim-açu river in Sergipe. Also concludes that the model applies satisfactorily in hydrological studies of the watershed in question. Regarding at Regional Development and the Environment, the study recommends more detailed research on the hydrogeological aspects of the region, aiming at quantitative and qualitative preservation of existing large underground spring, which represents an important meaning for human supply of Aracaju population and to maintaining the balance of coastal agroecosystems.